Melanoma immunotherapy: strategies to overcome pharmacological resistance. Issue 4 (2nd April 2020) - Trojaniello, Claudia; Vitale, Maria Grazia; Scarpato, Luigi; Esposito, Assunta; Ascierto, Paolo A.
ABSTRACT: Introduction : Although checkpoint inhibitors have provided a breakthrough in how melanoma is treated, about half of patients still do not respond due to primary or acquired resistance. New strategies are, therefore, required to increase the number of patients benefiting from immunotherapy. This systematic review investigates novel combinations that may overcome immune resistance in patients with melanoma. Areas covered : We provide an overview of immune-related resistance mechanisms and the various therapeutic strategies that can be considered in attempting to overcome these barriers, including combined immunotherapy approaches and combinations with chemotherapy, radiotherapy, and targeted therapy. Expert opinion : The immune response is a dynamic process in which the tumor microenvironment and immune cells interact in a variety of ways. New treatment approaches aim to enrich the tumor microenvironment with immune-infiltrate and increase response to immune checkpoint inhibitors.